Wild leafy plants market survey in Sicily: From local culture to food sustainability - Carla Zarbà; Valeria Allegra; Alfonso Silvio Zarbà; Giovanni Zocco (AIMS Agriculture and Food, 2019)
This study aimed to evaluate potential changes in habitual and occasional consumers in the use of wild plants in human nutrition. This objective was achieved towards research carried out in a territory rich on biodiversity and agricultural landscapes (wild plants strip), place of origin of many civilizations; that is, in Sicily. The results of a sample of 134 people—supported by discussions with local peddlers—have shown that the interest for human consumption of wild leafy ‘vegetables’ is widespread, so much so that these are included among new food lifestyles. Mainly nutritional aspects related to health, popular tradition and the sustainable perspective determine the value of these vegetables. The importance of preserving and enhancing the local edible flora emerges, if the relative market conditions (season nature of wild leafy plants; food supply chain) are in close synergy with the principles of the circular economy.